1997
DOI: 10.1002/(sici)1520-6408(1997)21:3<177::aid-dvg1>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of disrupting the gene that encodes α‐glucosidase II in the N‐linked oligosaccharide biosynthesis pathway of Dictyostelium discoideum

Abstract: We have identified and disrupted the gene coding for alpha-glucosidase II in Dictyostelium discoideum. This enzyme is responsible for removing two alpha 1,3-linked glucose residues from N-linked oligosaccharides on newly synthesized glycoproteins. Mutagenesis by restriction enzyme-mediated integration (REMI) generated a clone, DG1033, which grows well but forms abnormal fruiting bodies with short, thick stalks. The strain lacks alpha-glucosidase II activity and makes incompletely processed N-linked oligosaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Glucosidases are proposed to be crucial for ER quality control of glycoprotein folding and exit from the ER (Helenius and Aebi, 2001). In all systems studied to date, GIIa is encoded by a unique gene (Trombetta et al, 1996;Freeze et al, 1997;Simons et al, 1998). In the available U. maydis sequence, we have detected one gene with significant similarity to gas1 whose product shares with Gas1 the catalytic site motif of family-31 glycosyl hydrolases (Henrissat, 1991) (Broad Institute, http://www.broad.mit.edu/seq/; contig 1.92, position 7939-4835).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucosidases are proposed to be crucial for ER quality control of glycoprotein folding and exit from the ER (Helenius and Aebi, 2001). In all systems studied to date, GIIa is encoded by a unique gene (Trombetta et al, 1996;Freeze et al, 1997;Simons et al, 1998). In the available U. maydis sequence, we have detected one gene with significant similarity to gas1 whose product shares with Gas1 the catalytic site motif of family-31 glycosyl hydrolases (Henrissat, 1991) (Broad Institute, http://www.broad.mit.edu/seq/; contig 1.92, position 7939-4835).…”
Section: Discussionmentioning
confidence: 99%
“…The only other case where mutation in an a-glucosidase leads to a developmental defect is D. discoideum, where modA mutants are perfectly viable but produce stunted fruiting bodies with a short, thickened stalk. For this system, it has been speculated that correctly trimmed sugar chain structures in glycoproteins may be required for correct stalk assembly (Freeze et al, 1997). N-linked sugars of glycoproteins have been implicated in correct protein folding, secretion, and protein stability (Rademacher et al, 1988;Varki, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition or ablation of this enzyme is expected to prevent further processing by glycosidases and glycosyltransferases in the secretory pathway. Previous data on the Dictyostelium discoideum M31 glucosidase II mutant have indicated that radiolabelled N-glycans are increased in size (as judged by gel filtration) and have a decreased degree of sulphation and phosphorylation (as shown by anion-exchange chromatography) in comparison to the wild-type (15,24,47) . Our new mass spectrometric data confirm that the N-glycome of Dictyostelium is strongly affected in the M31 glucosidase II mutant; nevertheless, our study indicates that a remarkable degree of processing still takes place.…”
Section: The Glycomic Impact Of Inhibition or Ablation Of Glucosidase IImentioning
confidence: 97%
“…The Dictyostelium M31 mutant (16) was previously shown to be phenocopied by a specific mutation of the modA glucosidase II gene in the DG1033 strain as well as be rescued by transformation with the wild-type gene under control of an actin promoter (24) . However, the exact nature of the mutation in M31 was not known.…”
Section: Determination Of the Genetic Defect In The M31 Glucosidase Imentioning
confidence: 99%
See 1 more Smart Citation